Perceived Career Barriers among Female University Students in Nepal - Pokhrel , Sagar; Parajuli, Sujan (Adhyayan Journal, 2026)
Educational qualification is considered one of the major fundamental competencies in developing a successful career. Access to higher education and employability is closely associated by universities and policymakers. Increasing enrollment of female students in higher education has diversified the argument on female employment and the barriers to overcome for career advancements. This paper attempts to discuss the major career barriers considered by female university students and their awareness of overcoming such barriers. A descriptive study was conducted to analyze the responses of 162 female students studying BBA, BBS, and MBS in Bhadrapur, Jhapa, collected through a convenience sampling method. The study highlighted work-life balance and stereotypes about women as a major barrier to career planning. Skill development workshop and career counseling programs are identified as major support activities to help them better organize their career planning. The outcome suggests that dedication and educational qualifications are primary factors to achieve success in a professional environment.